2020
DOI: 10.1016/j.ymgmr.2020.100648
|View full text |Cite
|
Sign up to set email alerts
|

Combined donor-recipient genotypes of leptin receptor and adiponectin gene polymorphisms affect the incidence of complications after renal transplantation

Abstract: Background We aimed to examine whether combined donor/recipient variants in the leptin receptor ( LEPR ) and adiponectin ( ADIPOQ ) genes may affect outcomes in renal transplantation. Methods A total of 233 donors and their corresponding 307 recipients were genotyped for LEPR rs1805094, rs1137100 and rs1137101, and ADIPOQ rs1501299 and rs224176. Combined donor/rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Many studies demonstrated the association of SNP rs1501299 in adiponectin gene with adiponectin levels [ 19 , 25 ], but no association was found between rs1501299 and adiponectin levels in Italy [ 4 ] and Iran [ 35 ]. Studies have shown that SNP rs1501299 is associated with higher serum levels of Adiponectin [ 43 ], and it is a protective factor for diabetes Mellitus, hypertension, coronary artery disease, and dyslipidemia in American, Japanese, Finnish [ 35 ], and Korean populations [ 35 , 39 ]. No significant association was found between rs17366743 SNP and adiponectin concentration in Russian Federation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated the association of SNP rs1501299 in adiponectin gene with adiponectin levels [ 19 , 25 ], but no association was found between rs1501299 and adiponectin levels in Italy [ 4 ] and Iran [ 35 ]. Studies have shown that SNP rs1501299 is associated with higher serum levels of Adiponectin [ 43 ], and it is a protective factor for diabetes Mellitus, hypertension, coronary artery disease, and dyslipidemia in American, Japanese, Finnish [ 35 ], and Korean populations [ 35 , 39 ]. No significant association was found between rs17366743 SNP and adiponectin concentration in Russian Federation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression modeling was used to examine the influence of the SNPs on vascular CKD risk, adjusting for demographics and classic risk factors, namely age, sex, ethnicity, diabetes and hypertension, as formerly described [ 38 ]. After testing five inheritance models in the preliminary genetic analyses (codominant, dominant, recessive, overdominant, and log-additive), we decided to utilize the dominant model in the risk analysis, as we have done in former reports by our group [ 39 , 40 ], because the resulting genotype groups were the most balanced in terms of size and because it resulted in more significant associations. In order to examine the value of the studied SNPs in predicting susceptibility to CKD, receiving operating curves (ROC) were generated for models containing classic clinical and demographic risk factors adding or not the genetic information.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently published by Mann et al that nearly one-third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES [ 22 ]. For the first time, Mota-Zamorano and colleagues found that some variants in the LEPR and ADIPOQ genes of donors and recipients might affect the outcome of kidney transplantation [ 23 ]. Later, it was observed in several studies that ADIPOQ played an essential role in patients with post-transplant diabetes mellitus [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%